1992
DOI: 10.1159/000216311
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effect of Ticlopidine on He-Ne Laser-Induced Thrombus Formation in Rat Mesenteric Microvessels

Abstract: The inhibitory effects of ticlopidine and acetylsalicylic acid (ASA) on thrombus formation in rat mesenteric microvessels were studied. The results were compared with the effect of the drugs on platelet aggregation in citrated whole blood. He-Ne laser-induced thrombus formation in arterioles and in venules was significantly inhibited by 100 mg/kg ticlopidine. In contrast, a higher dose of ASA (300 mg/kg) was needed to inhibit thrombus formation and the effects of ASA were observed only in arterioles and not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The present study showed that the inhibitory effect of clopidogrel on platelet activation was approximately 30-fold stronger than that of ticlopidine, a finding similar to a previous report [11]. However, the present effective dose of ticlopidine was higher compared with that obtained in an in vivo study using rats [38]. The initial stimulus for platelet aggregation is undoubtedly shear stress in haemostatometry.…”
Section: Discussionsupporting
confidence: 87%
“…The present study showed that the inhibitory effect of clopidogrel on platelet activation was approximately 30-fold stronger than that of ticlopidine, a finding similar to a previous report [11]. However, the present effective dose of ticlopidine was higher compared with that obtained in an in vivo study using rats [38]. The initial stimulus for platelet aggregation is undoubtedly shear stress in haemostatometry.…”
Section: Discussionsupporting
confidence: 87%
“…The duration of the anti thrombotic effect of argatroban appeared to be longer in venules than in arterioles, and the results might reflect differences in the throm botic potential between the different micro vessels. A differential antithrombotic effect in mesenteric arterioles has also been observed after administration of acetylsalicylic acid [ 12].…”
Section: Discussionmentioning
confidence: 90%
“…Thrombi induced by an argon laser are easily disrupted by flow ing blood, and occlusive thrombi are rarely formed [7]. In contrast, thrombi formed with a He-Ne laser are usually completely occlu sive, and this method offers significant ad vantages for the study of thrombosis in situ [9][10][11][12],…”
Section: Introductionmentioning
confidence: 99%
“…For example the results of the Ticlopidine and Aspirin Stroke Study (TASS) indicated that both drugs were effective in the primary and secondary pre vention of stroke but that ticlopidine might have been more effective than ASA in these instances [12][13][14][15][16]. In addition, we have pre viously demonstrated that ticlopidine had a greater antithrombotic activity than ASA in an in vivo animal model using mesenteric microvessels [22], In the present study we compared ticlopidine and L-ASA in an in vivo model, using cerebral microvessels, and L-ASA showed as strong an antithrombotic effect as ticlopidine. The current results tended to indicate that L-ASA was more effec tive than ASA, since ASA inhibited thrombus formation only in mesenteric arterioles at 300 mg/kg and failed to inhibit it in venules in the previous study [22],…”
Section: Discussionmentioning
confidence: 99%
“…Microthrombi were formed using a He-Ne laser operated at a power of 20 mW (Nco-30 MS; Nihon Kagaku Eng., Osaka, Japan) in the presence of Evans blue [18,22], The laser beam was introduced into the operating microscope by a dichroic mirror and was directed through the optical path to the center of the microvessels. The diameter of the laser spot on the focal plane was 35 pm.…”
Section: Laser-induced Thrombus Formationmentioning
confidence: 99%